Characteristics of central nervous system progression in non‐small cell lung cancer treated with crizotinib or alectinib. Issue 6 (7th May 2021) - Sakamoto, Hiroaki; Yanagitani, Noriko; Manabe, Ryo; Tsugitomi, Ryosuke; Ogusu, Shinsuke; Tozuka, Takehiro; Yoshida, Hiroshi; Amino, Yoshiaki; Ariyasu, Ryo; Uchibori, Ken; Kitazono, Satoru; Tasaka, Sadatomo; et al.
Abstract: Background: Most patients treated with anaplastic lymphoma kinase ( ALK ) ‐tyrosine kinase inhibitors for ALK ‐positive non‐small cell lung cancer (NSCLC) develop resistance, leading to metastasis, with progression to the central nervous system (CNS) being a primary concern. Although alectinib has better CNS penetration than crizotinib, patients treated with alectinib also develop CNS progression. CNS metastases more likely occurs during crizotinib treatment due to less blood‐brain barrier (BBB) penetration capability than alectinib. CNS progression pattern may be different during crizotinib and alecitinib treatment. Understanding the characteristics of CNS progression is important for developing treatment strategies. Aims: We compared the clinical‐radiographic characteristics of CNS metastases among patients undergoing crizotinib and alectinib treatment for ALK ‐positive NSCLCs. Methods and results: We retrospectively analyzed the radiographic and clinical characteristics of CNS progression in ALK ‐positive NSCLC patients treated with crizotinib or alectinib at our hospital between July 2011 and May 2020. CNS and systemic tumor progression were evaluated using computed tomography or magnetic resonance imaging. Fifty‐three and 65 patients were treated with crizotinib and alectinib, respectively. Baseline CNS metastasis was observed in 18 and 27 patients in the crizotinib and alectinib groups, respectively. Among the patients in the crizotinib and alectinib groups who developed disease progression, 15/49 (30.6%) and 9/44 (20.5%) had CNS progression, respectively ( P  = .344). Intra‐CNS progression‐free survival was significantly longer in the alectinib group than in the crizotinib group (median: 14.0 vs 5.6 months, P  = .042). The number of CNS metastases sized ≥3 cm, rate of peritumoral brain edema, and the second progression pattern after treatment continuation was not significantly different between the groups. Conclusion: We observed no significant difference in the clinical‐radiographic characteristics of CNS progression between patients undergoing crizotinib and alectinib treatments. Local therapy, including stereotactic radiosurgery, for CNS progression may be suitable and important following alectinib and crizotinib treatment.